TRANSFORMASI PENENUN BUGIS-WAJO MENUJU ERA MODERNITAS - Syukur, dkk., Muhammad (History Department, Semarang State University and Historian Society of Indonesia, 2014)
This study aims to reveal the transformation process of weaving activity of Wajo people in South Sulawesi. This study uses a constructivist paradigm with a qualitative approach. Data was collected through in depth interviews, observation, documentation, and historical sociology. The analysis data uses data reduction, data presentation, and taking conclusion. The results shows that the weaving activities of Wajo people in design patterns and developing the loom stuffs by cultural fusion from outside of Bugis community and local elements of creativity and local intelligence communities of Wajo. The transformation process began with the use of a loom gedogan in the 13th century, then loom machines in 1950, and the use of looms machine in 2004. Pattern Transformation is begun from plain pattern (1400-1600), squares pattern/palekat (1600-1900), and the pictorial pattern (1900-now). Keywords: Transformation, Weaver, Bugis-WajoÂ Penelitian ini bertujuan mengungkapkan proses transformasi kegiatan tenun rakyat di Kabupaten Wajo Provinsi Sulawesi Selatan. Penelitian ini menggunakan paradigma konstruktivis dengan pendekatan kualitatif. Pengumpulan data di-lakukan dengan metode wawancara mendalam, observasi, dokumentasi, dan studi sosiologi sejarah. Analisis data menggunakan reduksi data, sajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kegiatan pertenunan rakyat di Kabupaten Wajo dalam menunjukkan adanya perpaduan kebudayaan dari luar komunitas Bugis dan unsur kreatifitas dan kecerdasan lokal masyarakat Wajo. Transformasi alat tenun bermula pada penggunaan alat tenun gedogan pada abad ke-13, kemudian Alat Tenun Bukan Mesin pada tahun 1950, dan penggunaan Alat Tenun Mesin tahun 2004. Transormasi corak bermula dari corak tidak bergambar (tahun 1400-1600), corak kotak-kotak/palekat (1600-1900), dan corak bergambar (1900-sekarang). Kata Kunci: Transformasi, Penenun, Bugis-Wajo Â Â